Secondary education student bodily practices: implications of gender in and outside physical education classes - Ferreira, Aline Fernanda [UNESP]; Rufino, Luiz Gustavo Bonatto [UNESP]; Diniz, Irlla Karla Dos Santos [UNESP]; Darido, Suraya Cristina [UNESP] (Universidade Estadual Paulista, 2016)
The present study aimed to analyze the bodily practices of high school students inside and outside of the physical education classes from the perspective of gender. A total of 426 students (63.7% girls and 36.3% boys) enrolled in the 2nd year of public high schools in a municipality in the interior of São Paulo State participated in the study. To collect the data, a questionnaire was elaborated and analyzed based on categories of survey and systematic cross-gender comparisons. The results showed that, in general, boys are more physically active than girls, regarding practices inside and outside of physical education classes. Distinctions were found regarding the bodily manisfestations chosen by each group, the behavior associated with the social and the cultural contexts to which boys and girls are exposed from birth to adult life.
Keywords: high school; gender; physical education; physical activity